2018
DOI: 10.1186/s12960-018-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

The status of licensed pharmacy workforce in Saudi Arabia: a 2030 economic vision perspective

Abstract: BackgroundThe economy of Saudi Arabia is currently undergoing a major transformation which will have an impact on employment in the pharmacy sector. However, quantitative data characterizing the pharmacy workforce in the Kingdom are currently not available. Therefore, the aim of this study was to determine the current status of the licensed pharmacy workforce in the pharmacy field in Saudi Arabia.MethodsDescriptive statistics were performed on data from the Saudi Commission for Health Specialties (SCFHS) as of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 11 publications
1
90
1
Order By: Relevance
“…In the present study, Less than 30% of HCPs believed that the clinical pharmacist has fulfilled his/her role in KSA. This may be due to lack of the clinical pharmacists in the hospitals (AlRuthia et al, 2018) which was supported by the findings of the present study where only 31.4% of the participants reported that they have a clinical pharmacist in their institutions. This lack is not limited to the hospitals of the ministry of health but also extends to the private hospitals.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, Less than 30% of HCPs believed that the clinical pharmacist has fulfilled his/her role in KSA. This may be due to lack of the clinical pharmacists in the hospitals (AlRuthia et al, 2018) which was supported by the findings of the present study where only 31.4% of the participants reported that they have a clinical pharmacist in their institutions. This lack is not limited to the hospitals of the ministry of health but also extends to the private hospitals.…”
Section: Discussionsupporting
confidence: 82%
“…Authority for Statistics, 2016). Secondly, there are about 32,500 registered pharmacists in Pakistan while registered pharmacists in Saudi Arabia are about 24,395 (Naqvi et al, 2017;AlRuthia et al, 2018). Therefore, pharmacy workforce density in Saudi healthcare system is higher as compared to Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…"… we might concentrate on fresh graduate students because those fresh graduate students have good knowledge and they are well trained and maybe offering those services will be run by them more than old pharmacists because attitude is di cult to change their practice...." (Pt19, M, [30][31][32][33][34][35][36][37][38][39]Govt. ) Participants also advocated for a better alignment between Saudi pharmacy curricula and pharmacy practice -with skills such as public health methods, patient psychology, communication and management lacking in the current highly clinical/scienti c curricula.…”
Section: Pharmacy Curricula and Ongoing Educationmentioning
confidence: 99%
“…There are several certi cations they need to get.…." (Pt11, M, [30][31][32][33][34][35][36][37][38][39]Govt. ) "….…”
Section: Pharmacy Curricula and Ongoing Educationmentioning
confidence: 99%
See 1 more Smart Citation